The importance of clinical experience in AI-assisted corneal diagnosis: verification using intentional AI misleading - Hiroki Maehara; Yuta Ueno; Takefumi Yamaguchi; Yoshiyuki Kitaguchi; Dai Miyazaki; Ryohei Nejima; Takenori Inomata; Naoko Kato; Tai-ichiro Chikama; Jun Ominato; Tatsuya Yunoki; Kinya Tsubota; et al. (Scientific Reports)
Abstract We developed an AI system capable of automatically classifying anterior eye images as either normal or indicative of corneal diseases. This study aims to investigate the influence of AI’s misleading guidance on ophthalmologists’ responses. This cross-sectional study included 30 cases each of infectious and immunological keratitis. Responses regarding the presence of infection were collected from 7 corneal specialists and 16 non-corneal-specialist ophthalmologists, first based on the images alone and then after presenting the AI’s classification results. The AI’s diagnoses were deliberately altered to present a correct classification in 70% of the cases and incorrect in 30%. The overall accuracy of the ophthalmologists did not significantly change after AI assistance was introduced [75.2 ± 8.1%, 75.9 ± 7.2%, respectively (P = 0.59)]. In cases where the AI presented incorrect diagnoses, the accuracy of corneal specialists before and after AI assistance was showing no significant change [60.3 ± 35.2% and 53.2 ± 30.9%, respectively (P = 0.11)]. In contrast, the accuracy for non-corneal specialists dropped significantly from 54.5 ± 27.8% to 31.6 ± 29.3% (P < 0.001), especially in cases where the AI presented incorrect options. Less experienced ophthalmologists were misled due to incorrect AI guidance, but corneal specialists were not. Even with the introduction of AI diagnostic support systems, the importance of ophthalmologist’s experience remains crucial.